The rationality principle as a universal grammar of economic explanations - Cheng LI (Editura ASE Bucuresti, 2020)
A universal grammar of economic explanations is characterized by the means-end rationality principle, which can be understood by drawing a conceptual distinction between its two facets: theoretical abstraction and empirical content. The former serves as a pure form of economic way of thinking and thus delimits the capacities of economists to perceive and understand the manifold human behaviour. The latter provides economists with objects of thought and renders the discipline empirically relevant. Given the implications of the two facets of rationality, the main task of economics as a descriptive science is to incorporate appropriate empirical content into the pure rational framework with the aim of better explaining and predicting human behaviour. As a prescriptive science, economic inquiry should draw on the persuasion and communication skills of its practitioners, thereby influencing the state of the economy through changing the means and ends of the decision makers in question.